Effects of Sodium and Chloride Source and Concentration on 15- to 25-lb Nursery Pig Growth Performance - D. J. Shawk; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 360 barrows (initially 15.6 lb; Line 200 × 400; DNA, Columbus, NE) were used in a 21-day trial to determine effects of source and concentration of dietary Na and Cl on nursery pig growth performance. Upon entry to the nursery, pigs were randomly allotted by body weight and fed a common starter diet (0.33% Na and 0.76% Cl) for 8 days. On day 8 after weaning, considered day 0 in the trial, pens were blocked by body weight and randomly assigned to 1 of 6 dietary treatments that were fed from day 0 to 14. Experimental treatments included two added salt diets (providing 0.13% Na and 0.35% Cl or 0.35% Na and 0.68% Cl), three diets with Na and Cl provided by NaHCO3and KCl (0.13, 0.35, or 0.57% Na and 0.50% Cl), or a diet with NaHCO3and CaCl2(0.35% Na and 0.50% Cl). From day 0 to 14, average daily gain (ADG) and average daily feed intake (ADFI) improved (quadratic,P<0.05) as dietary Na concentration increased from 0.13 to 0.35%, with no further benefits observed thereafter. Day 14 body weight tended (P<0.089) to increase as dietary Na concentration increased from 0.13 to 0.35%, with no further benefits observed thereafter. Feed efficiency (F/G) was not influenced by the dietary Na concentration. There was no evidence to indicate differences in growth performance due to Na or Cl source. From day 14 to 21 when pigs were fed a common diet, compensatory gain was observed with pigs previously fed low Na diets having increased (linear,P<0.05) ADG and improved F/G compared with pigs previously fed higher Na diets regardless of Na source. Previous source and concentration of Cl did not affect subsequent ADG. In conclusion, growth performance improved up to the Na concentration of 0.35% regardless of the dietary source of the Na and Cl ions.
Keywords: chloride; nursery pig; salt; sodium